Aging results in copper accumulations in glial fibrillary acidic protein‐positive cells in the subventricular zone. Issue 5 (8th July 2013) - Pushkar, Yulia; Robison, Gregory; Sullivan, Brendan; Fu, Sherleen X.; Kohne, Meghan; Jiang, Wendy; Rohr, Sven; Lai, Barry; Marcus, Matthew A.; Zakharova, Taisiya; Zheng, Wei
Summary: Analysis of rodent brains with X‐ray fluorescence (XRF) microscopy combined with immunohistochemistry allowed us to demonstrate that local Cu concentrations are thousands of times higher in the glia of the subventricular zone (SVZ) than in other cells. Using XRF microscopy with subcellular resolution and intracellular X‐ray absorption spectroscopy we determined the copper (I) oxidation state and the sulfur ligand environment. Cu K‐edge X‐ray absorption near edge spectroscopy is consistent with Cu being bound as a multimetallic Cu‐S cluster similar to one present in Cu‐metallothionein. Analysis of age‐related changes show that Cu content in astrocytes of the SVZ increases fourfold from 3 weeks to 9 months, while Cu concentration in other brain areas remain essentially constant. This increase in Cu correlates with a decrease in adult neurogenesis assessed using the Ki67 marker (both, however, can be age‐related effects). We demonstrate that the Cu distribution and age‐related concentration changes in the brain are highly cell specific.